A Study of Vibration Characteristics and Determination of the Conditions of Nanopores Formation in Metallic Materials during Laser Action. (2015) - Murzin, Serguei P.; Shakhmatov, Evgeniy V.; Igolkin, Alexander A.; Musaakhunova, Luiza F.
Abstract: The conditions of nanopores formation in metallic materials during the pulse-periodic laser action were determined. Laser action on two-component Cu-Zn alloy brass L62 was performed with using a CO2 laser ROFIN DC 010. Laser processing using pulse-periodic radiation with a pulse frequency in the range of 100 Hz to 5000 Hz enables the formation of a stable stress state on the sample surface at a temperature that does not exceed the melting point. The structure, containing open pores that fairly evenly distributed over the area, is formed during laser action to the surface of the metallic material. Branched pores with dendrite structure are also formed. The channel type nanopores with a width of ∼100 nm were formed under the chosen temperature-rate conditions, creating a nanoporous network. The formation of such structure is realized due to the creation of vacancies and their coagulation as a result of zinc sublimation from the surface of the material. This creates a concentration gradient and promotes diffusion to the surface of the component with relatively high vapour pressure. Measurement of vibration rate of the samples was performed. It was established that regardless of the external laser exposure frequency, the maximum values of the vibration rates of the forced oscillations of samples occur at almost the same frequencies corresponding to their natural oscillation frequencies, under these conditions, nanoporous structures are formed. Damping device application significantly reduces the vibration rate values. In this case the formation of the nanopores in the metallic material does not occur. It is determined that the intensity of formation nanopores in the studied metallic material depends on its vibration characteristics by laser action. The condition of nanopores formation is the presence of significant vibration of the sample.